LINGUISTIC ANALYSIS OF DIALOG ACTS IN THE CONTEXT OF FORENSIC INTERPRETATION OF INVESTIGATIVE ACTIONS (CASE STUDY: INTERVIEWS AND VERIFICATION OF STATEMENTS AT THE SCENE) - T. Berdnikova (Теория и практика судебной экспертизы, 2016)
The paper looks at the issues of linguistic analysis of dialogue between interviewee and investigator in situations of interrogation and verification of statements at the scene. It considers particular features of conversational interaction, indications of rehearsed speech, structural and semantic relationship between utterances, and characteristics of the speech material.